WEB-BASED INFORMATION SYSTEM FOR SALES OF PRODUCTS LABELED HALAL IN KHANZA ONLINE SHOP - Muhammad Rozzaq; Ade Eviyanti; Nuril Lutvi Azizah; Hindarto (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The times are getting more advanced, the price of necessities is also increasing, many elements justify any means to sell food/products that are not suitable for consumption in order to get abundant profits. which has neglected an important point, namely the halalness of the product. Therefore I made research on how to create an online shop that can sell halal products that are guaranteed to be halal. The Information Sistem for Sales of Halal Labeled Products at the Web-Based Khanza Online Shop is an online shop that sells products labeled as halal, the products being sold are products that have passed the test of the Indonesian Ulema Council (LPPOM MUI) Food and Drug Research Institute. Final result of This research is a sistem that makes it easier for Muslim communities in Indonesia, especially Sidoarjo, to be able to shop online for halal products that have been tested for halal